Porcine circovirus type 2 expression in the brain of neonatal piglets with congenital tremor. (July 2016) - Tummaruk, Padet; Pearodwong, Pachara
Abstract The present study demonstrates the presence of porcine circovirus type 2 (PCV2) antigen in the brains of neonatal piglets with congenital tremor. Piglets with clinical signs of congenital tremor were collected from a commercial swine herd for post-mortem examination. Brain tissue was collected from the piglets and was fixed in 10 % neutral buffered formalin, embedded in paraffin, and 4-μm thick sections were obtained. The PCV2 antigens were identified in the paraffin-embedded brain tissue sections by immunohistochemistry and light microscopy. The piglet preweaning mortality rates from birth to 14 and 21 days of age were 24.1 and 27.6 %, respectively. No typical gross lesions of PCV2 infection were observed in any of the piglets; however, PCV2 DNA was detected in the heart of a piglet. Immunostaining of PCV2 antigen was detected in neurons throughout the brain. It can be concluded that PCV2 antigen is present in the brain tissue of neonatal piglets with congenital tremor. Additional studies are required to determine the association between PCV2 expression and brain function.